O papel da comunicação no processo de transferência de tecnologia da Embrapa para a comunidade indígena Campo Alegre de Boa Vista, RR - Matos, Maria Lucilene Dantas de [UNESP] (2015)
This work consists of a study on the role of communication in the case of Embrapa with the indigenous community from Campo Alegre de Boa Vista, RR, under a technology transfer project. Its main purpose is to define communication strategies that facilitate the incorporation of sustainable technological innovations for tropical agriculture, focusing on the Campo Alegre indigenous community. The adopted research strategy was the case study using guidelines of participatory research and action research as a method. This work used as methodological instruments, unstructured interview, oral history and document analysis, as well as participant observation. Interpessonal and media communication resources were identified; concluded analysis of information flow and dialogue channels; verified appropriation of communication resources and recommended a systematic communication methodology for agricultural technology transfer to indigenous communities. The results show that technology transfer agents consiered the dynamics of own hierarchical system of indigenous culture with regard to the formal ans informal leardes. The flow of information passed over different levels. In that case, agents have appropriated communication resources and used different channels of dialogue for stakeholders. Communication strategies as those used in the project VAI facilitate the incorporation of sustainable technological innovations for tropical agriculture. The families involved in the technology transfer process incorporated the agricultural technological innovations proposed by Embrapa in their production system. The Campo Alegre indigenous community becomes a processing agent in its region. Community members who incorporated the new agricultural technologies are multipliers of scientific knowledge and contribute to local development